The positive feedback loop of furin and TGFβ1 enhances the immune responses of Tregs to hepatocellular carcinoma cells and hepatitis B virus in vitro. (11th April 2022) - Qiu, Hua; Wang, Na; Lin, Dongyi; Yuan, Ying; Li, Jinyuan; Mao, Dewen; Meng, Yinjie
Abstract: Regulatory T cells (Tregs) can exert immunosuppressive activity. Furin can regulate Treg functions, hepatitis B virus (HBV) persistent infection, and hepatocellular carcinoma (HCC) development. However, it remains unknown whether furin can regulate the immune responses of Tregs to HBV and HCC cells. Here, coculture systems of HBV1.3P‐HepG2.3P‐HepG2 cells and Tregs transduced with or without lentiviral particles that could overexpress furin or knockdown furin/transforming growth factor β1 (TGFβ1) were established to investigate the regulatory relationship between furin and TGFβ1 and the effect of furin/TGFβ1 on Treg activity. Also, the effects of furin overexpression or furin/TGFβ1 knockdown in Tregs on the immunological activity of effector T cells (Teffs)/cytotoxic T lymphocytes (CTLs) and HBV replication/expression were explored in the coculture system of Teff/CTL, Treg, and HBV1.3P‐HepG2 cells. Our results showed that furin expression and TGFβ1 secretion were notably increased in Tregs, and Furin and TGFβ1 formed a positive feedback loop to activate Tregs in the coculture system of Tregs and HBV1.3P‐HepG2 cells. Furin or TGFβ1 knockdown in Tregs promoted Teff cell proliferation, stimulated interleukin‐2 and interferon‐γ secretion, and inhibited HBV replication/gene expression in the coculture system of Teff, Treg, and HBV1.3P‐HepG2 cells. Moreover, furin or TGFβ1 depletion in Tregs enhanced the killing activity of CTLs against HBV1.3P‐HepG2 cells and curbed HBV replication/gene expression in the coculture system of Tregs, CTLs, and HBV1.3P‐HepG2 cells. In conclusion, the positive feedback loop of furin and TGFβ1 enhanced the immune responses of Tregs to HCC cells and HBV in vitro.